Antibacterial activity of Citrus Aurantium and Myrtus Communis extracts on some pathogenic bacteria - Anas Wisam Malik; Saja Mohammed Mohsen; Ali abbas abbod; sarmad Mohammad (Microbes and Infectious Diseases, 2025)
Background: Staphylococcus aureus, Staphylococcus epidermis, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, and Pseudomonas aeruginosa are regarded as harmful organisms. These germs exhibit resistance to multiple antibiotics; therefore, new therapies must be employed to combat the infection. Objectives: The antimicrobial efficacy of extracts from Citrus aurantium and Myrtus communis leaves was examined against bacteria. Methods: Between September 2023 - July 2024, a combined total of 50 clinical isolates were collected from cotton swabs taken from patients experiencing diabetic foot, respiratory infections, and urinary tract infections. Visiting specialized laboratories within the city of Baqubah, the diffusion method was employed to examine the impact of plant extracts on the development of the isolated bacteria under investigation. Results:   Ethanol extracts of Myrtus communis showed varying efficacy against S. aureus and S. epidermidis at concentrations of 100, 75, 50, 25, and 12.5 mg/ml, but extracts of Citrus aurantium exhibited ineffectiveness against both S. aureus and S. epidermidis at concentrations of 25 and 12.5 mg/ml. However, Citrus aurantium extract demonstrated efficacy at concentrations of 100, 75, and 50 mg/ml against both S. aureus and S. epidermidis, suppressing their growth with inhibition zones. Ethanol leaves extract of Myrtus communis and leaves extract of Citrus aurantium showed varying efficacy versus E. coli at concentrations of 25, 50, 75, and 100 mg/ml, whereas Myrtus communis was effective at a dose of 12.5 mg/ml. Conversely, Citrus aurantium at 12.5 mg/ml was ineffective against E. coli. All concentrations for Ethanol extracts of Myrtus communis and Ethanol leaves extract of Citrus aurantium were effective against the K. pneumoniae. Ethanol leaves extract of Myrtus communis and extracts of Citrus aurantium demonstrated varying efficacy against P. aeruginosa at concentrations of 50, 75, and 100 mg/ml, while concentrations of 25 and 12.5 mg/ml were ineffective. The ethanol extract of Myrtus communis showed varied efficacy against P. mirabilis in various concentrations, while the leaves extract of Citrus aurantium was not effective at all concentrations. Conclusion:  Our findings indicate that ethanol extracts from plant leaves (Citrus aurantium and Myrtus communis) possess the capability to function  as antibiotics against prevalent bacterial isolates responsible for infections in our community.